Analysis of Unlawful Acts by a Land Deed Official Concerning Promised Compensation in the Granting of Land Donations - Muhammad Faza Kamla Alfitra; Ria Fitri; Teuku Abdurrahman (Graha Primera Saintifika, 2026)
The transfer of land rights through grants must be evidenced by a deed executed before a Land Deed Official (PPAT), who is also obliged to explain the contents and legal implications of the deed to the parties concerned. In practice, however, grants accompanied by compensation frequently give rise to legal issues, particularly where the parties do not fully understand the legal nature and consequences of the transaction. This study aims to analyze the occurrence of land grants accompanied by compensation, the legal responsibility of PPATs, and the legal consequences arising from such transactions. Employing a normative juridical method, this research utilizes statutory, case, and conceptual approaches with qualitative legal analysis. The findings indicate that the PPAT’s failure to provide adequate explanations regarding the legal consequences of the deed is associated with a shift in the parties’ understanding of the legal nature of grants and may create conditions that contribute to legal uncertainty. From a legal perspective, grants accompanied by compensation may be regarded as inconsistent with the essential characteristics of a grant and, therefore, may affect the validity of the legal act. Accordingly, PPATs should provide comprehensive legal explanations to the parties, while reciprocal legal relationships should be structured through legal instruments that correspond to their actual legal characteristics to ensure legal certainty and minimize the risk of future disputes.